2011
DOI: 10.1111/j.1365-2044.2011.06817.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative respiratory and analgesic effects of dexmedetomidine or morphine for adenotonsillectomy in children with obstructive sleep apnoea

Abstract: Summary The postoperative respiratory and analgesic effects of dexmedetomidine and morphine have not been compared in children with sleep apnoea having adenotonsillectomy. In a randomised double‐blind study we recruited 60 children, aged 2–13 years, who received either intravenous dexmedetomidine 1 μg.kg−1 or morphine 100 μg.kg−1 on anaesthetic induction. End‐tidal carbon dioxide, Children’s Hospital of Eastern Ontario Pain Scale score and supplementary morphine administration were recorded every 15 min for 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 19 publications
1
28
1
1
Order By: Relevance
“…This makes dexmedetomidine a very attractive anesthetic, analgesic, and sedative adjuvant that will not have dose‐dependent synergist effects on respiration, unlike remifentanil or propofol. This and the opioid sparing analgesic effect of dexmedetomidine have proven to be beneficial in high‐risk pediatric patients such as children with obstructive sleep apnea undergoing tonsillectomy or as an adjunct to maintain adequate anesthesia and SV for removal of airway foreign body .…”
Section: Pharmacologymentioning
confidence: 99%
“…This makes dexmedetomidine a very attractive anesthetic, analgesic, and sedative adjuvant that will not have dose‐dependent synergist effects on respiration, unlike remifentanil or propofol. This and the opioid sparing analgesic effect of dexmedetomidine have proven to be beneficial in high‐risk pediatric patients such as children with obstructive sleep apnea undergoing tonsillectomy or as an adjunct to maintain adequate anesthesia and SV for removal of airway foreign body .…”
Section: Pharmacologymentioning
confidence: 99%
“…A single intraoperative bolus dose without subsequent infusion has been shown to reduce postoperative analgesic requirements , reduce emergence agitation , provide smoother extubation conditions , and successfully treat emergence delirium and postoperative shivering . Sedative effects without associated respiratory depression may be a particular advantage in children with obstructive sleep apnea undergoing adenotonsillectomy, who are at particular risk of opioid‐ and anesthetic‐induced respiratory complications postoperatively .…”
Section: Introductionmentioning
confidence: 99%
“…11 The RR of patients experiencing at least 1 desaturation episode was 1.63 times greater in patients who received morphine as compared to patients who received tramadol (95% CI: 0.64-6.13). An additional study by Zhuang and colleagues 12 reported no difference in the incidence of respiratory depression between patients receiving postoperative IV dexmedetomidine or IV morphine (p=0.85). Two different doses of IV tramadol compared to IV morphine were studied in a prospective, double-blind, RCT in children undergoing elective T&A.…”
Section: Resultsmentioning
confidence: 93%